Influence of Pseudomonas fluorescens strains producing ACC deaminase and indole acetic acid on germination traits and early seedling growth of barley cultivars under salinity stress - میترا آزادیخواه; فاطمه جمالی; حمیدرضا نوریزدان; فرشته بیات (علوم و فناوری بذر ایران, 2020)
In order to investigate the effect of different strains of Pseudomonas fluorescens with plant growth-promoting and salinity tolerance charachteristics on germination attributed traits and early growth of barley, a study was performed in Persian Gulf University, Bushehr. A factorial experiment was conducted with three factors of bacteria in four levels (P. fluorescens strains B10, B2-10, B2-11 and B4-6), salinity levels (0, 3 and 6 ds/m) and cultivar in five levels (Karun, Zehak, Nimrooz, South of the Sahra) in a completely randomized design with three replications. After a week, germination percentage and speed, seed vigor, length and dry weight of coleoptyl and radical and salinity tolerance index were measured. Results revealed that the main effect of bacteria, salinity and cultivars and their interactions were significant on all measured traits. Seed pre-treatment with all bacteria strains increased seed germination attributed traits, salinity tolerance index and seedling early growth were under salinity stress (P≤0.05). The current study confirms the ameliorative effect of indole acetic acid and ACC deaminase producing Pseudomonas strains on growth factors of barley seedlings under salt stress.